Gambaran Nilai Index Trombosit pada Pasien Tuberulosis Paru yang Mengonsumsi Obat Anti Tuberkulosis - Widiyanto, S.Y. Didik; Qomariyah, Nurul; Sofyanita, Eko Naning (Poltekkes Kemenkes Semarang, 2023)
Tuberculosis (TB) is a disease caused by the bacterium Mycobacterium tuberculosis which mostly attacks the lungs. Based on several studies, it is stated that tuberculosis sufferers who take OAT for healing experience side effects in the form of lowering the platelet index due to reactions from drugs that lyse platelets. This research is a descriptive study with a cross sectional design. Research was conducted on 30 respondents who consumed OAT. The results of this study obtained results of more than 50% on one of the platelet indices, namely the PWD value, which was obtained with low results with a total of 19 patients (63.3%), while for other indices such as platelet counts there were 21 patients (70%) , MPV in 28 patients (93%) and PCT in 23 patients (77%) had normal results. The conclusion of this study is that platelet index examinations in TB patients tend to be low in MPV and PDW, while they show high results in PLT and PCT examinations.